Design of teaching/learning sequences for the chemistry curriculum according to an inquiry-based approach - Cecilia Giordano (Firenze University Press, 2016)
Outlined are guidelines (teaching/learning sequences) for chemistry teachers in the first two years of secondary school. This educational proposal is grounded on an inquiry-based approach, and follows the spiral structure of the different levels of the chemistry concepts (from macroscopic to microscopic). Our aim is both the assessment of a more significant learning process and the achievement of some students' basic skills, as well as to provide teachers with a tool for implementation in class. The examples illustrated refer to the sequences relative to chemical transformation and the particle model. In closing, the results of a study are exhibited, which support the effectiveness of the proposed approach on the basis of the results obtained by the students.   Progettazione di sequenze didattiche di insegnamento/apprendimento della chimica secondo un approccio inquiry-based Viene illustrata la progettazione di linee guida (sequenze didattiche di insegnamento/apprendimento) per gli insegnanti di chimica nel primo biennio della scuola secondaria di secondo grado. Questa proposta didattica è concepita secondo un approccio inquiry-based, e segue la struttura a spirale dei diversi livelli di concettualizzazione della chimica (dal macroscopico al microscopico). Scopo del progetto è, da un lato, il miglioramento della significatività dell'apprendimento degli allievi e il raggiungimento di alcune competenze trasversali di base, dall'altro, fornire agli insegnanti uno strumento da utilizzare nella pratica di classe per implementare la trasposizione didattica della disciplina. Gli esempi illustrati riguardano le sequenze relative alla trasformazione chimica e al modello particellare. Vengono infine mostrati i risultati di uno studio che supporta l'efficacia dell'approccio proposto sulla base dei risultati conseguiti dagli allievi.